Wage Differentials Between the Public and Private Sector in India - Glinskaya, Elena; Lokshin, Michael (World Bank, Washington, DC, 2012)
The authors use 1993-94 and 1999-2000 India Employment and Unemployment surveys to investigate wage differentials between the public and private sectors as well as workers' decisions to join a particular sector. To obtain robust estimates of the wage differential, they apply three econometric techniques each relying on a different set of assumptions about the process of job selection. All three methods show that differences in wages between public sector workers and workers in the formal-private and informal-casual sectors are positive and high. Estimates show that, on average, the public sector premium ranges between 62 percent and 102 percent over the private-formal sector, and between 164 percent and 259 percent over the informal-casual sector, depending on the choice of methodology. The authors' review of wage differentials (estimated using similar methodologies) across the world shows that India has one of the largest differentials between wages of public workers and workers in the formal private sector. The wage differentials in India tend to be higher in rural as compared with urban areas, and are higher among women than among men. The wage differential also tends to be higher for low-skilled workers. There is considerable evidence of an increase in the wage differential between 1993-94 and 1999-2000.